2021
DOI: 10.1002/gj.4339
|View full text |Cite
|
Sign up to set email alerts
|

Depositional environment of polymictic conglomerate of the Gadag greenstone Belt, Western Dharwar Craton, south India: An insight for Neoarchean marginal sedimentation

Abstract: Clast morphometry and sedimentary facies analysis of polymictic conglomerate of the Hiriyur Formation in the Gadag greenstone Belt, Western Dharwar Craton, India, was conducted to constrain the palaeohydraulic condition, depositional environment, and type of sedimentary basin. The conglomerate grades from clast‐supported to matrix‐supported with siltstone‐sandstone intercalations. Eight lithofacies along with five major lithofacies associations are recognized in the Majjur and Attikatti Domains of the Gadag gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…In the measured section, the proportion of different clast compositions among the pebble‐ to boulder‐size clasts varies from place to place. It was observed that 30–50 volume percentages are of granitoid clasts (granite, granodiorite, TTG), 20–45 volume percentages of volcanic rocks (basalt, andesite, quartz porphyry), and 10–25 volume percentage of recycled sedimentary rocks (quartzite, BIF, argillite) (Table 1; and for details, refer Pratihari et al, 2021). Clasts are generally oblate to prolate in shape, well‐rounded to angular, with high sphericity (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the measured section, the proportion of different clast compositions among the pebble‐ to boulder‐size clasts varies from place to place. It was observed that 30–50 volume percentages are of granitoid clasts (granite, granodiorite, TTG), 20–45 volume percentages of volcanic rocks (basalt, andesite, quartz porphyry), and 10–25 volume percentage of recycled sedimentary rocks (quartzite, BIF, argillite) (Table 1; and for details, refer Pratihari et al, 2021). Clasts are generally oblate to prolate in shape, well‐rounded to angular, with high sphericity (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…Conglomerates from both the Attikatti and Majjur domains are polymictic and vary from clast‐ to matrix‐supported (Figure 4a,b). The matrix‐supported conglomerate constitutes 30%–34% of the total sediment succession, while the clast‐supported conglomerate constitutes 22%–27% (Pratihari et al, 2021). The matrix‐supported conglomerate grade from pebble poor to pebble rich (nearly in rhythmic manner; Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations